Evaluation of grain yield, and quality characteristics of some bread wheat cultivars in different agro-ecological regions of Türkiye - Bekir Aktaş; Halil İbrahim Gökdere (Heliyon)
Climate change and recurrent droughts challenge wheat production and yield, necessitating careful selection and plant breeding research. ''Value for Cultivation and Use'' experiments are crucial for assessing genetic gains and providing information about potential pathways to alleviate production losses under specific environmental conditions. The goal of the study was to compare the grain yield and quality characteristics of 46 registered bread wheat cultivars in 5 out of 7 agro-ecological regions of Türkiye between 2016-2017 and 2017–2018. The registered wheat cultivars were also characterized in terms of high molecular weight glutenin subunits (HMW-GS) and the relationships between quality traits and band patterns. Genotype × environment interaction was found statistically significant (p < 0.05) for grain yield and the stability of the cultivars as explained on biplot graphs. The Mediterranean and the Central Anatolian region had the highest and the lowest average grain yield of 8137 kg ha−1 and 4260 kg ha−1 respectively under the rainfed conditions. The average thousand kernel weight of the cultivars was 35.3–39.9 g, with test weight of 77.2–79.2 kg hL−1, protein content of 13.4–14.7 %, Zeleny sedimentation of 39.2–53.3 mL, and alveograph energy value varied between 191.2-276.4 × 10−4 J. The most common subunits in cultivars were 2∗ at Glu-A1, 7 + 8 and 7 + 9 at Glu-B1, and 5 + 10 at Glu-D1. It is concluded that high-quality new varieties are developed by high-molecular-weight glutenin subunits oriented crosses and selections in Turkish wheat breeding programs.